2016
DOI: 10.15441/ceem.15.118
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficiency of emergency department interrogation of cardiac devices

Abstract: ObjectivePatients with implanted cardiac devices may wait extended periods for interrogation in emergency departments (EDs). Our purpose was to determine if device interrogation could be done safely and faster by ED staff.MethodsProspective randomized, standard therapy controlled, trial of ED staff device interrogation vs. standard process (SP), with 30-day follow-up. Eligibility criteria: ED presentation with a self-report of a potential device related complaint, with signed informed consent. SP interrogation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 11 publications
0
7
0
4
Order By: Relevance
“…Earlier studies have demonstrated that CIED interrogation results in a low (~10%) rate of reprogramming 2,3. ED disposition is frequently delayed because of questions surrounding CIED functionality 4. The current accepted practice for CIED evaluation is to have the device interrogated by an IBHRE‐certified professional, often a company representative.…”
Section: Characteristics Total (N = 182) Pf (N = 155) Fr (N = 27)mentioning
confidence: 99%
See 4 more Smart Citations
“…Earlier studies have demonstrated that CIED interrogation results in a low (~10%) rate of reprogramming 2,3. ED disposition is frequently delayed because of questions surrounding CIED functionality 4. The current accepted practice for CIED evaluation is to have the device interrogated by an IBHRE‐certified professional, often a company representative.…”
Section: Characteristics Total (N = 182) Pf (N = 155) Fr (N = 27)mentioning
confidence: 99%
“…The current accepted practice for CIED evaluation is to have the device interrogated by an IBHRE‐certified professional, often a company representative. Because these representatives can be based hours away from hospitals, requesting their services can result in substantial delays in care 4. In addition, inpatient physicians are wary to admit patients whose devices may require immediate intervention and also resist “admissions for interrogation” because these often require no action.…”
Section: Characteristics Total (N = 182) Pf (N = 155) Fr (N = 27)mentioning
confidence: 99%
See 3 more Smart Citations